2015
DOI: 10.1063/1.4926730
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of super-structure domain walls in two dimensional assemblies of magnetic nanoparticles

Abstract: We simulate the formation of domain walls in two-dimensional assemblies of magnetic nanoparticles. Particle parameters are chosen to match recent electron holography and Lorentz microscopy studies of almost monodisperse cobalt nanoparticles assembled into regular, elongated lattices. As the particles are small enough to consist of a single magnetic domain each, their magnetic interactions can be described by a spin model in which each particle is assigned a macroscopic “superspin.” Thus, the magnetic behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…In low-dimensional (1-2D) systems, electron holography studies have revealed both nearest neighbor and overall FM-like ordering [33] in long and narrow ensembles in both close-packed as well as more disordered nanoparticle ensembles. In thicker nanoparticle structures, long-range AFM-like interactions become important, as evidenced by super-spin domain formation, with sharp 180 degree walls between nearest neighbor cores [34,35]. Experimental evidence for nearest neighbor moment correlations within ordered 3D arrays of magnetic cores was obtained by Faure et al [36], using dynamic magnetometry in combination with Monte-Carlo simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In low-dimensional (1-2D) systems, electron holography studies have revealed both nearest neighbor and overall FM-like ordering [33] in long and narrow ensembles in both close-packed as well as more disordered nanoparticle ensembles. In thicker nanoparticle structures, long-range AFM-like interactions become important, as evidenced by super-spin domain formation, with sharp 180 degree walls between nearest neighbor cores [34,35]. Experimental evidence for nearest neighbor moment correlations within ordered 3D arrays of magnetic cores was obtained by Faure et al [36], using dynamic magnetometry in combination with Monte-Carlo simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Most theoretical work on supermagnetism, more specifically on dipolar-coupled magnetic lattices, treat regular arrays with a well-defined lattice symmetry, [11][12][13][14] where the individual dipolar-coupled nanomagnets are assumed to be monodomain. 15 In the present study, we explore supermagnetism in arrays of 5 nm thick circular nanomagnets using the micromagnetic simulation software MuMax3. 16 This is an open-source GPU-accelerated code that solves the Landau-Lifshitz equation.…”
mentioning
confidence: 99%
“…The magnetic moments of the three states (F, T, L) were allowed to relax using damped Newtonian dynamics (see Supplementary Information and ref. 28 for details). The initial states of the elongated structures relax to somewhat similar states (i.e., we do not observe transitions between the three states during relaxation).…”
Section: Magnetic Simulations and Discussionmentioning
confidence: 99%